Electrode assembly and lithium secondary battery

By forming polymer or ceramic particle coating with high zeta potential on the separator of lithium secondary batteries and using flame retardant electrolytes, the problem of short circuit and fire at high temperatures is solved, and its safety and electrochemical performance are improved performance.

CN119278529APending Publication Date: 2025-01-07LG ENERGY SOLUTION LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202380041761.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-09-05
Filing Date
2023-09-06
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

Lithium secondary batteries are prone to ignite due to short circuits between the positive electrode and the negative electrode in high temperature environments, and the prior art is difficult to effectively improve their high temperature safety and electrochemical properties.

Method used

The coating with polymer particles or ceramic particles with an absolute value of zeta potential of more than 25mV is used to form on the surface of the membrane, and by adjusting the adhesion and thickness of the coating to the membrane, the membrane is ensured that the membrane is not easy to shrink at high temperature, and preventing the positive electrode and The negative electrode is short-circuited, and the flame retardant electrolyte is used to improve lithium ion mobility.

Benefits of technology

It effectively improves the high-temperature safety and electrochemical performance of lithium secondary batteries, prevents fire caused by short circuits, maintains lithium ion conductivity, and extends the battery life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119278529A_ABST
    Figure CN119278529A_ABST
Patent Text Reader

Abstract

The electrode assembly according to the present invention comprises: a positive electrode; a negative electrode; a separator disposed between the positive electrode and the negative electrode; and a coating layer formed on one surface of the separator, in which a 90 DEG peel strength between the separator and the coating layer measured at 60 DEG C is 30 gf / 25 mm to 140 gf / 25 mm.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] CROSS-REFERENCE TO RELATED APPLICATIONS

[0002] This application claims the priority of Korean Patent Application No. 10-2022-0113106 filed in the Korean Intellectual Property Office on September 6, 2022, and Korean Patent Application No. 10-2023-0117680 filed in the Korean Intellectual Property Office on September 5, 2023, the disclosures of which are incorporated herein by reference in their entirety.

[0003] The present disclosure relates to an electrode assembly and a lithium secondary battery. Background Art

[0004] As technology develops and demand for electric vehicles and energy storage systems (ESS) increases, demand for batteries as energy sources has rapidly increased, and therefore, various studies have been conducted on batteries that can meet various needs. In particular, research on lithium secondary batteries with excellent life and cycle characteristics and high energy density has been actively conducted as a power source for such devices.

[0005] Generally, a lithium secondary battery includes a positive electrode, a negative electrode, a separator between the positive electrode and the negative electrode, an electrolyte, etc. Since the positive electrode may generate oxygen due to its unstable structure in a charged state, and the risk of fire is high when oxygen is generated, attempts have been made to study and develop methods capable of enhancing the safety of lithium secondary batteries.

[0006] The separator is used to ensure electrical insulation between the positive electrode and the negative electrode, and a film made of polyolefin is generally used. However, polyolefin-based separators tend to shrink in high temperature environments and therefore cannot insulate between the positive and negative electrodes. When electrical insulation between the positive and negative electrodes becomes impossible, a short circuit may occur, which may interact with the oxygen generated by the unstable positive electrode to cause a fire. In other words, when a short circuit occurs in a charged lithium secondary battery in a high temperature environment, there is a problem of a lithium secondary battery catching fire.

[0007] Therefore, there is a need to develop a technology related to a method capable of enhancing the high temperature safety of lithium secondary batteries. Summary of the invention

[0008] Technical issues

[0009] The present disclosure provides an electrode assembly and a lithium secondary battery including the same, the electrode assembly improving the high temperature stability of the lithium secondary battery and also maintaining excellent electrochemical performance.

[0010] Technical Solution

[0011] According to one embodiment of the present disclosure, an electrode assembly is provided, which includes: a positive electrode; a negative electrode; a separator disposed between the positive electrode and the negative electrode; and a coating formed on one surface of the separator and comprising polymer particles or ceramic particles having an absolute value of a zeta potential of 25 mV or more, wherein a 90° peel strength between the separator and the coating measured at 60°C is 30 gf / 25 mm to 140 gf / 25 mm.

[0012] In the electrode assembly, the coating may be in direct contact with the positive electrode.

[0013] In the electrode assembly, a ratio D1 / D2 of a thickness of the coating layer (D1) to a thickness of the separator (D2) may be 0.1 to 4.

[0014] In the electrode assembly, the thickness (D1) of the coating layer may be 30 μm or less.

[0015] In the electrode assembly, the thickness (D2) of the separator may be 5 μm to 20 μm.

[0016] In the electrode assembly, the polymer particles having an absolute value of zeta potential of 25 mV or more may include at least one selected from the group consisting of polyethylene oxide (PEO), polyphenylene sulfide (PPS), polyalkyl (meth)acrylate, polystyrene, polyvinyl chloride, polycarbonate, polysulfone, polyethersulfone, polyetherimide, polyphenylsulfone, polyamideimide, polyimide, polybenzimidazole, polyetherketone, polyphthalamide, polybutylene terephthalate and polyethylene terephthalate.

[0017] In addition, the ceramic particles may include at least one selected from the group consisting of boehmite (γ-AlO(OH)), Al2O3, TiO2, Fe2O3, SiO2, ZrO2, Co3O4, SnO2, NiO, ZnO, V2O5, MnO, LAGP (lithium aluminum germanium phosphate) based compounds, LLZO (lithium lanthanum zirconium oxide) based compounds, LATP (lithium aluminum titanium phosphate) based compounds, LLZTO (lithium lanthanum zirconium tantalum oxide) based compounds, LLTO (lithium lanthanum titanium oxide) based compounds, LSTP (lithium silicon titanium phosphate) based compounds, LGPO (lithium germanium phosphate) based compounds and lithium oxide (e.g., Li2O).

[0018] The polymer particles or ceramic particles may have an average particle size (D 50 ). In addition, the coating may include a polymer binder, and polymer particles or ceramic particles dispersed on the polymer binder, wherein the coating may include a polymer binder:polymer particles in a weight ratio of 1:9 to 5:5, or the coating may include a polymer binder:ceramic particles in a weight ratio of 1:9 to 5:5.

[0019] According to another embodiment of the present disclosure, a lithium secondary battery is provided, including: the electrode assembly described above, and a flame retardant electrolyte containing a flame retardant solvent having a flash point of 100° C. or more or having no flash point, and a lithium salt.

[0020] In this case, the flame retardant solvent may include at least one organic solvent selected from the group consisting of: a sulfone functional group, a fluorine-containing functional group, a phosphorus-containing functional group and a nitrile functional group. More specifically, the flame retardant solvent may include at least one organic solvent selected from the group consisting of: a sulfone compound, a nitrile compound, a phosphoric acid compound and a fluorine-substituted carbonate compound.

[0021] Technical Effects

[0022] In the case of an electrode assembly according to the present disclosure, the 90° peel strength between the separator and the coating measured at 60°C is 30gf / 25mm to 140gf / 25mm. When the adhesion between the separator and the coating satisfies the above range, the separator bonded to the coating is not easy to shrink even in a high temperature environment, thereby preventing a short circuit between the positive and negative electrodes, which can improve the high temperature safety of the lithium secondary battery. In addition, when the adhesion between the separator and the coating satisfies the above range, the pores in the separator are excessively blocked by the particles contained in the coating, thereby minimizing the problems of reduced lithium ion conductivity at the interface between the separator and the coating and increased cell resistance.

[0023] In addition, since the polymer particles and / or ceramic particles contained in the coating have a relatively high melting point compared to the polyolefin-based polymer, the coating containing these particles is not easy to shrink even at high temperatures. Therefore, the coating suppresses the thermal shrinkage of the separator, thereby preventing the short circuit between the positive electrode and the negative electrode at high temperatures, which can improve the high temperature safety of the lithium secondary battery.

[0024] On the other hand, when a flame retardant electrolyte is used to ensure the high temperature safety of a lithium secondary battery, the flame retardant electrolyte has the following problems: it has low impregnation into a polyolefin-based separator, resulting in a decrease in lithium ion mobility in the separator. However, when the coating formed on the separator of the present invention comprises polymer particles and / or ceramic particles having an absolute value of zeta potential of 25 mV or more, the coating is easily impregnated with the flame retardant electrolyte, thereby ensuring lithium ion mobility. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 is a graph showing the voltage-temperature change over time of the lithium secondary battery manufactured in Example 1.

[0026] Figure 2 is a graph showing the voltage-temperature change over time of the lithium secondary battery manufactured in Example 2.

[0027] Figure 3 is a graph showing the voltage-temperature change over time of the lithium secondary battery manufactured in Example 3.

[0028] Figure 4 is a graph showing the voltage-temperature change over time of the lithium secondary battery manufactured in Example 4.

[0029] Figure 5 is a graph showing the voltage-temperature change over time of the lithium secondary battery manufactured in Comparative Example 1.

[0030] Figure 6 is a graph showing the voltage-temperature change over time of the lithium secondary battery manufactured in Comparative Example 2.

[0031] Figure 7 is a graph showing the voltage-temperature change over time of the lithium secondary battery manufactured in Comparative Example 3.

[0032] Figure 8 is a graph showing the voltage-temperature change over time of the lithium secondary battery manufactured in Comparative Example 4.

[0033] Fig. 9 is a graph showing the voltage-temperature change over time of the lithium secondary battery manufactured in Comparative Example 5. DETAILED DESCRIPTION

[0034] By referring to the detailed description and drawings of the following preferred embodiments, the advantages and features of the present disclosure and the methods for implementing the present disclosure can be more easily understood. However, the present disclosure can be implemented in many different forms and should not be interpreted as being limited to the embodiments set forth herein. On the contrary, these embodiments are provided to make the present disclosure more thorough and complete and to fully convey the concept of the present invention to those skilled in the art, and the present disclosure will only be limited by the appended claims. The same reference numerals will be used throughout to refer to the same or similar elements.

[0035] Unless otherwise defined, all terms (including technical and scientific terms) used herein may be used as the meanings that are generally understood by those skilled in the art to which the present disclosure belongs. In addition, unless clearly specifically defined, terms defined in commonly used dictionaries will not be ideally or overly interpreted.

[0036] The terms used herein are provided to describe the embodiments, but are not intended to limit the inventive concept. In the specification, unless the context clearly indicates otherwise, the singular includes the plural. The terms "include" and / or "comprising" used herein do not exclude the presence or addition of one or more elements other than the mentioned elements.

[0037] In addition, throughout the description, when a part is referred to as “including” or “comprising” a certain component, unless otherwise specified, it means that the part can further include other components, rather than excluding the other components.

[0038] The term "and / or" used herein in phrases such as "A and / or B" is intended to include "A" (alone) or "B" (alone) or "both A and B".

[0039] Unless expressly stated otherwise, as used herein, the term "%" refers to wt. %.

[0040] As used herein, D 50 D refers to the particle size at which the cumulative volume of particles reaches 50% in the particle size distribution curve of the particles. D can be measured using, for example, laser diffraction. 50 Laser diffraction methods can generally measure particle sizes from the submicrometer range to the several millimeters range and can obtain results with high reproducibility and high resolution.

[0041] As used herein, the 90° peel strength between the separator and the coating is measured by the following procedure: a separator having a coating formed on one surface thereof is prepared to have a width of 25 mm, a double-sided tape is then attached to a glass slide, rolled twice with a 2 kg roller, and the coating is peeled off from the separator at a separation distance of 90 mm at a speed of 300 mm / min under a temperature condition of 60°C, and the average value of the 90° peel strength is measured.

[0042] As used herein, "zeta potential" is an indicator indicating the degree of surface charge of a particle. The zeta potential of a particle in the present disclosure can be measured, for example, by an electrophoretic light scattering method using a dynamic light scattering device. Specifically, the zeta potential of a polymer particle or a ceramic particle can be measured by an electrophoretic light scattering method after the polymer particle is dispersed in water or an alcohol-based solvent without a dispersant.

[0043] Now, embodiments of the present disclosure will be described in detail.

[0044] <Electrode assembly>

[0045] An electrode assembly according to an embodiment of the present disclosure includes a positive electrode, a negative electrode, a separator disposed between the positive electrode and the negative electrode, and a coating formed on one surface of the separator and containing polymer particles or ceramic particles having an absolute value of a zeta potential of 25 mV or more, wherein a 90° peel strength between the separator and the coating measured at 60° C. is 30 gf / 25 mm to 140 gf / 25 mm.

[0046] The coating may be formed on one surface of the separator. In this case, the 90° peel strength between the separator and the coating measured at 60°C may be 30gf / 25mm to 140gf / 25mm, specifically 35gf / 25mm to 135gf / 25mm, and more specifically 35gf / 25mm to 100gf / 25mm. If the 90° peel strength between the separator and the coating measured at 60°C is too small, the adhesion between the separator and the coating is weak. Therefore, when the separator heat shrinks at high temperatures, the positive and negative electrodes may cause a short circuit, accompanied by the risk of battery fire. If the 90° peel strength between the separator and the coating measured at 60°C is too large, the pores in the separator will be excessively blocked by the particles contained in the coating, thereby minimizing the problem of reduced lithium ion conductivity at the interface between the separator and the coating and increased cell resistance.

[0047] In an electrode assembly of one embodiment, the coating may directly contact the positive electrode. In this case, a separator is provided between the coating and the negative electrode so that the coating may not directly contact the negative electrode. Therefore, the coating directly contacts the negative electrode, so that the irreversible reaction of the polymer in the coating during battery operation can be prevented from being reduced and decomposed, thereby preventing the problem of deterioration of the cycle life characteristics of the battery.

[0048] The ratio D1 / D2 of the thickness of the coating (D1) to the thickness of the separator (D2) may be 0.1 to 4, specifically 0.2 to 3, and more specifically 0.3 to 2. If D1 / D2 is less than 0.1, the coating is too thin relative to the separator, and sufficient adhesion between the separator and the coating cannot be ensured, so the separator may thermally shrink at high temperatures. If D1 / D2 is greater than 4, the coating is too thick relative to the separator, and the lithium ion conductivity in the coating is reduced, which may increase the cell resistance.

[0049] On the other hand, when only a coating layer is provided between the positive electrode and the negative electrode without a separator in the electrode assembly, the thickness of the coating layer must be made larger to prevent a short circuit between the positive electrode and the negative electrode. However, when a coating layer and a separator are used together in an electrode assembly as in the above-mentioned embodiment, the thickness of the coating layer can be formed thinner on the separator.

[0050] Specifically, the thickness (D1) of the coating layer may be 30 μm or less, preferably 1 μm to 20 μm, and more preferably 3 μm to 15 μm. If the thickness of the coating layer satisfies the above range, sufficient adhesion between the separator and the coating layer can be ensured to prevent the separator from shrinking at high temperatures and prevent short circuits between the positive and negative electrodes.

[0051] In the electrode assembly of the above embodiment, the coating on the separator may include at least one of polymer particles or ceramic particles having an absolute value of zeta potential of 25 mV or more.

[0052] At this time, the zeta potential of polymer particles or ceramic particles is an indicator of the degree of surface charge of these particles, which can define electrostatic repulsion, dispersibility between particles, etc. Polymer particles or ceramic particles with large absolute values ​​of zeta potential can be evenly dispersed on the separator to show satisfactory and uniform coating performance, and a large number of fine and uniform pores that allow lithium ions to pass between these particles can be defined. In addition, since the particles meet such a zeta potential, the coating can show excellent impregnation of a flame retardant electrolyte containing a flame retardant solvent. Due to the combination of this coating and a flame retardant electrolyte, a lithium secondary battery including an electrode assembly of an embodiment can show excellent electrochemical properties.

[0053] For example, the zeta potential of polymer particles or ceramic particles can be measured by electrophoretic light scattering using a dynamic light scattering device. In this case, the zeta potential of polymer particles or ceramic particles can be measured in a state where the particles are dispersed in water or an alcohol-based solvent without a separate dispersant. In a specific example, the zeta potential can be measured in a state where the polymer particles are dispersed in an aqueous solvent at a concentration of 0.1 wt.% or less.

[0054] The absolute value of the zeta potential of the polymer particles or ceramic particles can be 25mV or more, or 35mV or more, or 45mV or more, and 100mV or less, or 90mV or less, or 80mV or less. Within this range, satisfactory coating performance and porosity of the coating can be achieved, and high impregnation performance of the flame retardant electrolyte can be ensured, so that a uniform reaction occurs throughout the middle electrode, thereby improving various properties of the lithium secondary battery such as capacity, output and life characteristics.

[0055] Specific examples of the polymer particles may include at least one selected from the group consisting of polyethylene oxide (PEO), polyalkyl (meth)acrylate, polystyrene, polyvinyl chloride, polycarbonate, polysulfone, polyethersulfone, polyetherimide, polyphenylsulfone, polyamideimide, polyimide, polybenzimidazole, polyetherketone, polyphthalamide, polybutylene terephthalate and polyethylene terephthalate.

[0056] In addition, specific examples of the ceramic particles include at least one selected from the group consisting of boehmite (γ-AlO(OH)), Al2O3, TiO2, Fe2O3, SiO2, ZrO2, Co3O4, SnO2, NiO, ZnO, V2O5, and MnO.

[0057] In another example, the ceramic particles may be ceramic particles containing lithium and having ion conductivity, such as lithium oxide or lithium phosphorus oxide particles. Specific examples of the ceramic particles include at least one selected from the group consisting of LAGP (lithium aluminum germanium phosphate) based compounds, LLZO (lithium lanthanum zirconium oxide) based compounds, LATP (lithium aluminum titanium phosphate) based compounds, LLZTO (lithium lanthanum zirconium tantalum oxide) based compounds, LLTO (lithium lanthanum titanium oxide) based compounds, LSTP (lithium silicon titanium phosphate) based compounds, LGPO (lithium germanium phosphate) based compounds, and lithium oxides (e.g., Li2O).

[0058] The zeta potential of polymer particles or ceramic particles can be adjusted not only by the type of each particle, but also by the particle size or surface characteristics of these particles. Therefore, in order to achieve the zeta potential or dispersibility of polymer particles or ceramic particles, the appropriate porosity of the coating, etc., the average particle size D of the polymer particles or ceramic particles is preferably 50 It may be 300 nm to 3 μm, or 500 nm to 2.5 μm, or 700 nm to 2 μm.

[0059] Furthermore, in order to control the surface properties of the polymer particles or ceramic particles and thereby adjust the zeta potential or the like, the polymer particles or ceramic particles may be contained in the coating layer in a state where the surface has been treated with oxygen plasma or ion beams.

[0060] On the other hand, coating can have the structure including polymer binder and polymer particles or ceramic particles dispersed on polymer binder.At this point, polymer binder used herein can be the polymer of the same type as the binder included in the electrode active material layer, and its specific example can include polyvinylidene fluoride, polyvinyl alcohol, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinyl pyrrolidone, polytetrafluoroethylene, polyethylene (PE), polypropylene, ethylene-propylene-diene monomer, sulfonated ethylene-propylene-diene monomer, nitrile rubber (such as hydrogenated nitrile rubber), styrene-butadiene rubber, fluororubber etc., can also use two or more mixtures or copolymers selected from these polymers.However, the specific composition of polymer binder can be considered by those skilled in the art the type and characteristic of polymer particles or ceramic particles, the method for forming porous coating etc., obviously determined.

[0061] Furthermore, considering the excellent coating properties and porosity of the porous coating and the excellent dispersibility of the particles, the coating may include a weight ratio of polymer binder:polymer particles or polymer binder:ceramic particles of 1:9 to 5:5, or 2:8 to 4:6.

[0062] The above-mentioned coating layer may have electrical insulating properties. In addition, the coating layer may correspond to a porous insulating layer.

[0063] In addition, the coating has the property of not easily shrinking even at high temperatures. Therefore, when the separator having the coating formed thereon is applied to an electrode assembly, a short circuit between the positive electrode and the negative electrode can be prevented even under high temperature conditions, thereby improving the high temperature safety of the electrode.

[0064] On the other hand, the coating layer may be formed by forming a coating layer containing polymer particles or ceramic particles and a polymer binder on the separator to apply the composition, followed by drying and roll-pressing.

[0065] In this case, the solid content of the composition for forming the coating layer may be 19 wt.% to 25 wt.%, specifically 19 wt.% to 23 wt.%, more specifically 19 wt.% to 21 wt.%. When the solid content of the composition for forming the coating layer satisfies the above numerical range, the composition for forming the coating layer may have a viscosity at a level that can be coated on the diaphragm.

[0066] The viscosity of the composition for forming the coating layer at 25° C. may be, for example, 1000 cP to 10000 cP at room temperature, specifically 2000 cP to 7000 cP, more specifically 3000 cP to 5000 cP. When the viscosity of the composition for forming the coating layer satisfies the above numerical range, the composition for forming the coating layer may be coated on the separator with a uniform thickness.

[0067] On the other hand, in order to ensure that the coating layer can exhibit the above-mentioned peel strength range for the separator, the coating layer can be formed by applying the composition for forming the coating layer on the separator, followed by drying and rolling. At this time, the drying can be performed at a temperature of, for example, 60° C. to 150° C. for 0.5 to 12 hours. In addition, after such drying, the coating layer can be formed at 85 kg / cm 2 Up to 160kg / cm 2 or 90kg / cm 2 Up to 150kg / cm 2 For example, 2 to 4 or 2 to 3 roll pressings are performed under a pressure of 100 kg / cm2. When the pressure during the roll pressing is greater than 100 kg / cm2, the roll pressing is performed under a pressure of 100 kg / cm2. 2 And less than 160kg / cm 2 When the rolling is performed twice or three times, the rolling is preferably performed. As the drying and rolling process proceeds, a coating is formed on the separator to have a predetermined peel strength, so that a lithium secondary battery including an electrode assembly of an embodiment can exhibit improved high temperature stability and excellent electrochemical performance.

[0068] On the other hand, the separator can be used without particular limitation as long as it is generally used as a separator in a lithium secondary battery. Specifically, a separator having high moisture retention capability for an electrolyte and low resistance to the movement of electrolyte ions is preferred.

[0069] For example, as separator, can use the porous polymer film or its two or more layers of laminated structure comprising polyolefin-based polymer, polyolefin-based polymer such as ethylene homopolymer, propylene homopolymer, ethylene / butene copolymer, ethylene / hexene copolymer and ethylene / methacrylate copolymer.In addition, typical porous nonwoven fabric (for example, the nonwoven fabric formed by glass fiber, polyethylene terephthalate fiber etc. with high melting point) can be used as separator.

[0070] The thickness D2 of the separator may be 5 μm to 20 μm, preferably 5 μm to 15 μm, and more preferably 6 μm to 13 μm. If the thickness of the separator satisfies the above range, a short circuit between the positive electrode and the negative electrode can be prevented while minimizing the resistance value of the battery cell. As a result, the energy density of the lithium secondary battery can be prevented from decreasing and its life characteristics can be improved.

[0071] On the other hand, the positive electrode may include a positive electrode collector and a positive electrode active material layer formed on the positive electrode collector.

[0072] The positive electrode current collector is not particularly limited as long as it has conductivity and does not cause chemical changes in the battery. For example, the current collector can be formed of stainless steel, aluminum, nickel, titanium, calcined carbon, or aluminum, or aluminum or stainless steel surface-treated with carbon, nickel, titanium, silver, etc.

[0073] The positive electrode current collector may have a thickness of 3 μm to 500 μm, and fine protrusions and depressions may be formed on its surface to enhance the adhesion of the positive electrode active material layer. For example, the positive electrode current collector may be used in various forms such as: film, sheet, foil, net, porous body, foam, and non-woven fabric structure.

[0074] The positive electrode active material layer may include a positive electrode active material, and may optionally further include a conductive material, a binder, and the like.

[0075] The positive electrode active material may be a compound capable of reversibly inserting and deinserting lithium, and specifically, it may include a compound containing lithium and at least one metal (such as iron, cobalt, manganese, nickel or aluminum), such as a lithium metal oxide or a lithium metal phosphate. More specifically, these compounds may include lithium manganese-based oxides (e.g., LiMnO2, LiMn2O4, etc.), lithium cobalt-based oxides (e.g., LiCoO2, etc.), lithium nickel-based oxides (e.g., LiNiO2, etc.), lithium nickel manganese-based oxides (e.g., LiNi 1- Y Mn Y O2 (where 0 <Y<1)、LiMn 2-Z Ni ZO4 (where 0 < Z < 2, etc.), lithium nickel cobalt-based oxides (e.g., LiNi 1-Y1 Co Y1 O2 (where, 0 < Y1 < 1, etc.), lithium manganese cobalt-based oxides (e.g., LiCo 1-Y2 Mn Y2 O2 (where, 0 < Y2 < 1), LiMn 2-Z1 Co Z1 O4 (where, 0 < Z1 < 2, etc.), lithium nickel manganese cobalt-based oxides (e.g., Li(Ni p Co q Mn r )O2 (where, 0 < p < 1, 0 < q < 1, 0 < r < 1, and p + q + r = 1) or Li(Ni p1 Co q1 Mn r1 )O4 (where, 0 < p1 < 2, 0 < q1 < 2, 0 < r1 < 2, and p1 + q1 + r1 = 2) etc.), lithium nickel cobalt transition metal (M) oxides (e.g., Li(Ni p2 Co q2 Mn r2 M s2 )O2 (where, M is selected from the group consisting of Al, Fe, V, Cr, Ti, Ta, Mg, and Mo, and p2, q2, r2, and s2 are the atomic fractions of each independent element, where, 0 < p2 < 1, 0 < q2 < 1, 0 < r2 < 1, 0 < s2 < 1, and p2 + q2 + r2 + s2 = 1) etc.), lithium iron phosphate (e.g., Li 1+a Fe 1-x M x (PO 4-b )X b (where, M is at least one selected from Al, Mg, and Ti, X is at least one selected from F, S, and N, -0.5 ≤ a ≤ +0.5, 0 ≤ x ≤ 0.5, 0 ≤ b ≤ 0.1) etc.), and any one of them, or a compound of two or more of them can be used.

[0076] Among these compounds, in terms of improving the capacity characteristics and stability of the battery, the lithium metal oxides can include LiCoO2, LiMnO2, LiNiO2, lithium nickel manganese cobalt oxides (e.g., Li(Ni 1 / 3 Mn 1 / 3 Co 1 / 3 )O2, Li(Ni 0.6 Mn 0.2 Co 0.2 )O2, Li(Ni 0.5 Mn 0.3 Co 0.2 )O2, Li(Ni0.7 Mn 0.15 Co 0.15 )O2 and Li(Ni 0.8 Mn 0.1 Co 0.1 )O2, etc.), lithium nickel cobalt aluminum oxide (e.g., Li(Ni 0.8 Co 0.15 Al 0.05 )O2, etc.) or lithium nickel manganese cobalt aluminum oxide (e.g., Li(Ni 0.86 Co 0.05 Mn 0.07 Al 0.02 )O2), or lithium iron phosphate (e.g., LiFePO4), etc., and any single one or a mixture of two or more thereof may be used.

[0077] The content of the positive electrode active material may be 60 wt.% to 99 wt.%, preferably 70 wt.% to 99 wt.%, more preferably 80 wt.% to 98 wt.%, based on the total weight of the positive electrode active material layer.

[0078] The positive electrode conductive material is a component that further improves the conductivity of the positive electrode active material. This conductive material is not particularly limited as long as it has conductivity and does not cause chemical changes in the battery. For example, conductive materials such as the following can be used: carbon powder, such as carbon black, acetylene black, Ketjen black, channel black, furnace black, lamp black or thermal black; graphite powder, such as natural graphite, artificial graphite or graphite with a developed crystal structure; conductive fibers, such as carbon fibers or metal fibers; fluorinated carbon powder; conductive powders, such as aluminum powder and nickel powder; conductive whiskers, such as zinc oxide whiskers and potassium titanate whiskers; conductive metal oxides, such as titanium oxide; or polyphenyl derivatives.

[0079] Generally, the content of the positive electrode conductive material may be 1 wt.% to 20 wt.%, preferably 1 wt.% to 15 wt.%, more preferably 1 wt.% to 10 wt.%, based on the total weight of the positive electrode active material layer.

[0080] The positive electrode binder is a component that helps the active material and the conductive material to bond with each other and with the current collector.

[0081] Examples of such binders may include polyvinylidene fluoride, polyvinyl alcohol, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinyl pyrrolidone, polytetrafluoroethylene, polyethylene (PE), polypropylene, ethylene-propylene-diene monomer, sulfonated ethylene-propylene-diene monomer, styrene-butadiene rubber, fluororubber, various copolymers, and the like.

[0082] Generally, the content of the positive electrode binder may be 1 wt.% to 20 wt.%, preferably 1 wt.% to 15 wt.%, more preferably 1 wt.% to 10 wt.%, based on the total weight of the positive electrode active material layer.

[0083] On the other hand, the negative electrode may include a negative electrode current collector and a negative electrode active material layer formed on the negative electrode current collector. Alternatively, the negative electrode may include a graphite electrode made of carbon (C). Alternatively, the negative electrode may contain lithium metal or may be a metal current collector itself.

[0084] The negative electrode current collector is not particularly limited as long as it has high conductivity and does not cause chemical changes in the battery, and for example, copper, stainless steel, aluminum, nickel, titanium, calcined carbon, copper or stainless steel surface-treated with one of carbon, nickel, titanium, silver, etc., aluminum-cadmium alloy, etc. can be used.

[0085] The negative electrode current collector may generally have a thickness of 3 μm to 500 μm. In addition, similar to the positive electrode current collector, the negative electrode current collector may have fine protrusions and depressions formed on its surface to enhance the adhesion of the negative electrode active material. For example, the negative electrode current collector may be used in various forms such as: a film, a sheet, a foil, a mesh, a porous body, a foam, and a non-woven fabric structure.

[0086] The negative electrode active material layer may include a negative electrode active material, and may optionally further include a conductive material, a binder, and the like.

[0087] The negative electrode active material may include at least one selected from the group consisting of lithium metal, carbon materials capable of reversibly intercalating / deintercalating lithium ions, metals or alloys of lithium and these metals, metal composite oxides, materials that may be doped and undoped with lithium, and transition metal oxides.

[0088] As a carbon material capable of reversibly embedding / de-embedding lithium ions, any carbon material can be used without particular limitation, as long as it is a carbon-based negative electrode active material commonly used in lithium ion secondary batteries, and as a typical example, crystalline carbon, amorphous carbon or both can be used. An example of crystalline carbon can be graphite, such as irregular, planar, flaky, spherical or fibrous natural graphite or artificial graphite, and an example of amorphous carbon can be soft carbon (low temperature calcined carbon) or hard carbon, mesophase pitch carbide and sintered coke.

[0089] As the metal or the alloy of lithium and these metals, a metal selected from the group consisting of Cu, Ni, Na, K, Rb, Cs, Fr, Be, Mg, Ca, Sr, Si, Sb, Pb, In, Zn, Ba, Ra, Ge, Al and Sn, or an alloy of lithium and these metals can be used.

[0090] One kind selected from the group consisting of the following can be used as the metal composite oxide: PbO, PbO2, Pb2O3, Pb3O4, Sb2O3, Sb2O4, Sb2O5, GeO, GeO2, Bi2O3, Bi2O4, Bi2O5, Li x Fe2O3(0≤x≤1), Li x WO2(0≤x≤1) and Sn x Me 1-x Me' y O z (Me: Mn, Fe, Pb, Ge; Me': Al, B, P, Si, elements of Groups I, II, and III in the periodic table, or halogens; 0 < x ≤ 1; 1 ≤ y ≤ 3; 1 ≤ z ≤ 8).

[0091] The materials that can be doped with and without lithium can include: Si, SiO x (0 < x ≤ 2), Si - Y alloy (where Y is an element selected from the group consisting of: alkali metals, alkaline earth metals, Group 13 elements, Group 14 elements, transition metals, rare earth elements, and combinations thereof, and is not Si), Sn, SnO2, and Sn - Y (where Y is an element selected from the group consisting of: alkali metals, alkaline earth metals, Group 13 elements, Group 14 elements, transition metals, rare earth elements, and combinations thereof, and is not Sn), and a mixture of SiO2 and at least one of them can be used. The element Y can be selected from the group consisting of: Mg, Ca, Sr, Ba, Ra, Sc, Y, Ti, Zr, Hf, Rf, V, Nb, Ta, Db, Cr, Mo, W, Sg, Tc, Re, Bh, Fe, Pb, Ru, Os, Hs, Rh, Ir, Pd, Pt, Cu, Ag, Au, Zn, Cd, B, Al, Ga, Sn, In, Ge, P, As, Sb, Bi, S, Se, Te, Po, and combinations thereof.

[0092] The transition metal oxides can include lithium - containing titanium composite oxide (LTO), vanadium oxides, lithium vanadium oxides, etc.

[0093] Based on the total weight of the negative electrode active material layer, the content of the negative electrode active material can be 60 wt.% to 99 wt.%, preferably 70 wt.% to 99 wt.%, more preferably 80 wt.% to 98 wt.%.

[0094] The negative electrode conductive material is a component that further improves the conductivity of the positive electrode active material. This conductive material is not particularly limited as long as it has conductivity and does not cause chemical changes in the battery. For example, conductive materials such as: carbon powder, such as carbon black, acetylene black, Ketjen black, channel black, furnace black, lamp black or thermal black; graphite powder, such as natural graphite, artificial graphite or graphite with a developed crystal structure; conductive fibers such as carbon fibers or metal fibers; fluorinated carbon powder; conductive powders such as aluminum powder and nickel powder; conductive whiskers such as zinc oxide whiskers and potassium titanate whiskers; conductive metal oxides such as titanium oxide; or polyphenyl derivatives.

[0095] The negative electrode conductive material may be contained in an amount of 1 wt.% to 20 wt.%, preferably 1 wt.% to 15 wt.%, more preferably 1 wt.% to 10 wt.%, based on the total weight of the negative electrode active material layer.

[0096] The negative electrode binder is a component that assists the bonding between the negative electrode conductor, the negative electrode active material and the negative electrode current collector. Examples of such binders may include polyvinylidene fluoride (PVDF), polyvinyl alcohol, starch, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinyl pyrrolidone, polyethylene, polypropylene, ethylene-propylene-diene monomer and sulfonated ethylene-propylene-diene monomer, styrene-butadiene rubber, fluororubber, and various copolymers thereof.

[0097] Generally, the content of the negative electrode binder may be 1 wt.% to 20 wt.%, preferably 1 wt.% to 15 wt.%, more preferably 1 wt.% to 10 wt.%, based on the total weight of the negative electrode active material layer.

[0098] When the metal itself is used without forming a negative electrode active material layer on the negative electrode, it can be manufactured by physically combining, rolling or depositing the metal on the metal film itself or the negative electrode current collector. As a deposition method, an electrodeposition method or a chemical vapor deposition method of the metal can be used.

[0099] For example, the metal film itself or the metal bonded / rolled / deposited on the negative electrode current collector may include one type of metal selected from the group consisting of lithium (Li), nickel (Ni), tin (Sn), copper (Cu), and indium (In), or an alloy of two types thereof.

[0100] <Lithium Secondary Battery>

[0101] Next, a lithium secondary battery according to another embodiment of the present disclosure will be described.

[0102] Such a lithium secondary battery may include the electrode assembly described above and a flame retardant electrolyte. In this case, the electrode assembly is as described above.

[0103] The flame retardant electrolyte can be a non-volatile and non-flammable electrolyte. Specifically, the flame retardant electrolyte can be defined as an electrolyte comprising a flame retardant solvent having a flash point of 100°C or above or without a flash point and a lithium salt. At this time, the flame retardant solvent can include a substantially insoluble organic solvent without a flash point, and an organic solvent with a high flash point of 100°C or above, or 100°C to 250°C, or 110°C to 200°C and low volatility. The lithium secondary battery of other embodiments includes a flame retardant electrolyte containing such a flame retardant solvent and a lithium salt, so that excellent high temperature stability can be exhibited. According to the standard method of ASTM D3278, a closed tester or an open tester can be used to measure the flash point of the flame retardant solvent.

[0104] On the other hand, the flame retardant electrolyte has the problem of reducing the impregnation of the separator (e.g., polyolefin-based separator) used for lithium secondary batteries, thereby reducing the mobility of lithium ions in the separator. However, when the coating formed on the separator includes polymer particles and / or ceramic particles with a zeta potential absolute value of more than 25mV, it is easy to impregnate the coating with a flame retardant electrolyte to ensure lithium ion mobility. Therefore, various electrochemical characteristics of lithium secondary batteries can be well achieved.

[0105] The flame retardant electrolyte may include a flame retardant solvent and a lithium salt. In this case, the flame retardant solvent may serve as a medium through which ions involved in an electrochemical reaction of the battery cell may move.

[0106] In a specific example, the flame retardant solvent can be an organic solvent having a functional group selected from a functional group consisting of a functional group that contributes to the low volatility and flame retardancy or non-flammability of the organic solvent, such as a fluorine-containing functional group (such as a sulfone functional group and a fluorine-substituted hydrocarbon group), and a phosphorus-containing functional group (such as a phosphate group or a phosphonic acid group), and a nitrile functional group, and one or more such organic solvents can be mixed and used. More specifically, the flame retardant solvent can include at least one organic solvent selected from the group consisting of a sulfone-based compound, a nitrile-based compound, a phosphate-based compound, and a fluorine-substituted carbonate-based compound.

[0107] Among them, the sulfone compound may include at least one selected from the group consisting of cyclic sulfone compounds or linear sulfone compounds, specifically, the sulfone compound may include at least one selected from the group consisting of cyclopentane sulfone, tetramethylene sulfone, dibutyl sulfone, ethyl vinyl sulfone, methyl propyl sulfone, ethyl-i-propyl sulfone, ethyl-i-butyl sulfone, i-propyl-i-butyl sulfone, i-propyl-s-butyl sulfone and butyl-i-butyl sulfone.

[0108] In addition, the nitrile-based compound may include at least one selected from the group consisting of acetonitrile, succinonitrile, adiponitrile, malononitrile, glutaronitrile, suberonitrile, and sebaconitrile.

[0109] In addition, the phosphate-based compound may include at least one selected from the group consisting of dimethyl methyl phosphate, trimethyl phosphate, triethyl phosphate, tributyl phosphate, diethyl phosphate, dimethyl methyl phosphate, dimethyl (2-methoxyethoxy) methyl phosphonate, diethyl (2-methoxyethoxy) methyl phosphonate, and triphenyl phosphate.

[0110] In addition, the fluorine-substituted carbonate-based compound may include at least one selected from the group consisting of bis(2,2,3,3-tetrafluoro-propyl)carbonate, methyl-2,2,2-trifluoroethyl carbonate, ethyl-2,2,2-trifluoroethyl carbonate, propyl-2,2,2-trifluoroethyl carbonate, methyl-2,2,2,2',2',2'-hexafluoro-i-propyl carbonate, ethyl-2,2,2,2',2',2'-hexafluoro-i-propyl carbonate, di-2,2,2-trifluoroethyl carbonate, 2,2,2-trifluoroethyl-N,N-dimethyl carbonate, hexafluoro-i-propyl-N,N-dimethyl carbonate, 4-(2,2,3,3-tetrafluoropropoxymethyl)-[1,3]-dioxolane-2-one and bis(2,2,3,3-pentafluoro-propyl)carbonate.

[0111] On the other hand, lithium salts are used as media for transporting ions in lithium secondary batteries. For example, lithium salts may include Li + as a cation, and may include at least one selected from the group consisting of: F - , Cl - Br - ,I - 、NO3 - 、N(CN)2 - 、BF4 - 、ClO4 - , B 10 Cl 10 - 、AlCl4 - 、AlO2 - PF6 - CF3SO3 - 、CH3CO2 - CF3CO2 - 、AsF6 - 、SbF6 - 、CH3SO3 - 、(CF3CF2SO2)2N - 、(CF3SO2)2N - 、(FSO2)2N - 、BF2C2O4 - , BC4O8 - PF4C2O4 -PF2C4O8 - 、(CF3)2PF4 - 、(CF3)3PF3 - 、(CF3)4PF2 - 、(CF3)5PF - 、(CF3)6P - 、C4F9SO3 - CF3CF2SO3 - CF3CF2(CF3)2CO - 、(CF3SO2)2CH - CF3(CF2)7SO3 - and SCN - .

[0112] Specifically, the lithium salt may include a single material selected from the group consisting of LiCl, LiBr, LiI, LiBF4, LiClO4, LiB 10 Cl 10 , LiAlCl4, LiAlO2, LiPF6, LiCF3SO3, LiCH3CO2, LiCF3CO2, LiAsF6, LiSbF6, LiCH3SO3, LiFSI (lithium bis(fluorosulfonyl)imide, LiN(SO2F)2), LiBETI (lithium bis(perfluoroethanesulfonyl)imide, LiN(SO2CF2CF3)2, and LiTFSI (lithium bis(trifluoromethanesulfonyl)imide, LiN(SO2CF3)2), but from the perspective of excellent stability, LiN(SO2CF3)2 is preferably included. In addition to these, lithium salts commonly used in electrolytes of lithium secondary batteries can be used without limitation.

[0113] The concentration of the lithium salt can be appropriately changed within a generally available range, but the lithium salt can be included in the flame retardant electrolyte at a concentration of 1M to 3M in the electrolyte, preferably at a concentration of 1M to 2.5M, and more preferably at a concentration of 1M to 2M, to obtain the best effect of forming a film for preventing corrosion on the electrode surface. When the concentration of the lithium salt satisfies the above range, the effect of improving the cycle characteristics of the lithium secondary battery during high temperature storage is sufficient, and the viscosity of the flame retardant electrolyte is appropriate, so that the impregnation performance of the flame retardant electrolyte can be improved.

[0114] The lithium secondary battery can be manufactured by inserting the electrode assembly into a cylindrical battery case or a square battery case and then injecting a flame retardant electrolyte. Alternatively, the lithium secondary battery can be manufactured by impregnating the electrode assembly with a flame retardant electrolyte and then placing the resulting product into a battery case and sealing the case.

[0115] As the battery case, a commonly used battery case in the art can be used, and the shape is not limited according to the application of the battery. For example, the battery case can be cylindrical, square, pouch, coin-shaped, etc., but is not limited thereto.

[0116] The lithium secondary battery according to another embodiment of the present disclosure can be used not only as a battery cell used as a power source for a small device, but also preferably as a unit cell of a medium or large battery module including a plurality of battery cells. Preferred examples of medium or large devices include electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, and energy storage systems (ESS).

[0117] Hereinafter, the present disclosure will be described in more detail with reference to specific examples. However, the following examples are only exemplary embodiments for promoting understanding of the present invention and are not intended to limit the scope of the present invention. It is obvious to those skilled in the art that various variations and modifications may be made to the present invention without departing from the scope and spirit of the present disclosure, and these variations and modifications certainly fall within the scope of the appended claims.

[0118] Examples and Comparative Examples

[0119] First, in the following example, the zeta potential of the polymer particles or ceramic particles is measured by the electrophoretic light scattering method using a dynamic light scattering device (product name: ELS-Z) in a state where the polymer particles or ceramic particles are dispersed in an aqueous solvent at a concentration of less than 0.1 wt.% at a temperature of 25°C.

[0120] In addition, according to the standard method of ASTM D93, the flash point of the (flame retardant) organic solvent contained in the (flame retardant) electrolyte is measured by a closed tester. Specifically, the sample container is filled with the organic solvent sample, the container is covered with a lid and sealed, and then the sample container is heated at a constant rate according to the above standard method. During heating, the sample container is opened regularly to check whether a flame is generated, and the temperature at the time point of flame generation is measured as the flash point.

[0121] Example 1

[0122] (1) Production of diaphragm-coating composition

[0123] A separator made of polyolefin (thickness: 10 μm) was prepared.

[0124] The zeta potential is -50 mV and the average particle size is D 50Polymethyl methacrylate (PMMA) polymer particles with a size of 1 μm, hydrogenated nitrile rubber (H-NBR) and polyvinylidene fluoride (PVDF) were put into N-methyl-2-pyrrolidone (NMP) solvent and dispersed in a weight ratio of 7:1:2 to prepare a composition for forming a coating (solid content: 21 wt.%, viscosity: 4000 cP).

[0125] The composition for forming a coating layer was coated on a polyolefin separator (thickness: 10 μm), then dried at 80° C. for 1 hour and heated at 100 kg / cm 2 The separator was rolled twice at a pressure of 100 μm, thereby preparing a separator-coating composition in which a coating layer having a thickness of 10 μm was formed on one surface of the separator.

[0126] (2) Preparation of electrode assembly

[0127] A copper (Cu) metal film having a thickness of 20 μm was prepared as a negative electrode current collector, and a negative electrode active material layer containing artificial graphite as a negative electrode active material was formed on one surface of the copper metal film, thereby manufacturing a negative electrode having a thickness of 75 μm.

[0128] An aluminum (Al) metal film with a thickness of 15 μm was prepared as a positive electrode current collector, and a Li (Ni 0.8 Mn 0.1 Co 0.1 )02 is used as a positive electrode active material layer of the positive electrode active material, thereby manufacturing a positive electrode with a thickness of 60μm.

[0129] The coating layer formed on one surface of the separator is in contact with the positive electrode, and the other surface of the separator is in contact with the negative electrode to prepare an electrode assembly.

[0130] (3) Manufacturing of lithium secondary batteries

[0131] Li(N(SO2CF3)2(LiFSI) was dissolved in a flame retardant solvent sulfolane (flash point: about 165°C) at a concentration of 1.5 M to prepare a flame retardant electrolyte. A lithium secondary battery was manufactured by accommodating an electrode assembly in a battery case and then injecting the flame retardant electrolyte therein.

[0132] Example 2

[0133] The separator-coating composition was produced in the same manner as in Example 1, except that the composition for forming a coating layer was applied to the separator, then dried at 80° C. for 1 hour, and heated at 100 kg / cm 2 The film was rolled four times at a pressure of 1000 ℃ to form a coating layer with a thickness of 8 μm on one surface of the separator.

[0134] An electrode assembly and a lithium secondary battery were manufactured in the same manner as in Example 1, except that the separator-coating composition prepared by the above method was used.

[0135] Example 3

[0136] The separator-coating composition was produced in the same manner as in Example 1, except that the composition for forming a coating layer was applied to the separator, then dried at 80° C. for 1 hour, and heated at 90 kg / cm 2 The film was rolled twice at a pressure of 1000 ℃ to form a coating with a thickness of 11 μm on one surface of the separator.

[0137] An electrode assembly and a lithium secondary battery were manufactured in the same manner as in Example 1, except that the separator-coating composition prepared by the above method was used.

[0138] Example 4

[0139] The separator-coating composition was produced in the same manner as in Example 1, except that the composition for forming a coating layer was applied to the separator, then dried at 80° C. for 1 hour, and heated at 150 kg / cm 2 The film was rolled twice at a pressure of 1000 ℃ to form a coating with a thickness of 7 μm on one surface of the separator.

[0140] An electrode assembly and a lithium secondary battery were manufactured in the same manner as in Example 1, except that the separator-coating composition prepared by the above method was used.

[0141] Comparative Example 1

[0142] A separator made of polyolefin (thickness: 10 μm) was prepared.

[0143] An electrode assembly and a lithium secondary battery were manufactured in the same manner as in Example 1, except that a separator having no coating formed on one surface was placed in contact between the positive electrode and the negative electrode.

[0144] Comparative Example 2

[0145] The separator-coating composition was produced in the same manner as in Example 1, except that the composition for forming a coating layer was applied to the separator, then dried at 80° C. for 1 hour, and heated at 60 kg / cm 2 The film was rolled twice at a pressure of 1000 ℃ to form a coating with a thickness of 12 μm on one surface of the separator.

[0146] An electrode assembly and a lithium secondary battery were manufactured in the same manner as in Example 1, except that the separator-coating composition prepared by the above method was used.

[0147] Comparative Example 3

[0148] The separator-coating composition was produced in the same manner as in Example 1, except that the composition for forming a coating layer was applied to the separator, then dried at 80° C. for 1 hour, and heated at 200 kg / cm 2 The film was rolled twice at a pressure of 1000 ℃ to form a coating layer with a thickness of 6 μm on one surface of the separator.

[0149] An electrode assembly and a lithium secondary battery were manufactured in the same manner as in Example 1, except that the separator-coating composition prepared by the above method was used.

[0150] Comparative Example 4

[0151] The separator-coating composition was produced in the same manner as in Example 1, except that the composition for forming a coating layer was applied to the separator, then dried at 80° C. for 1 hour, and heated at 80 kg / cm 2 The film was rolled twice at a pressure of 1000 ℃ to form a coating with a thickness of 11.5 μm on one surface of the separator.

[0152] An electrode assembly and a lithium secondary battery were manufactured in the same manner as in Example 1, except that the separator-coating composition prepared by the above method was used.

[0153] Comparative Example 5

[0154] The separator-coating composition was produced in the same manner as in Example 1, except that the composition for forming a coating layer was applied to the separator, then dried at 80° C. for 1 hour, and heated at 150 kg / cm 2 The film was rolled four times at a pressure of 1000 ℃ to form a coating layer with a thickness of 6.5 μm on one surface of the separator.

[0155] An electrode assembly and a lithium secondary battery were manufactured in the same manner as in Example 1, except that the separator-coating composition prepared by the above method was used.

[0156] Experimental Example 1-Evaluation of the peel strength between the separator and the coating

[0157] For the separator-coating compositions prepared in Examples 1 to 4 and Comparative Examples 1 to 5, the 90° peel strength between the separator and the coating was measured.

[0158] Specifically, the membrane-coating compositions produced in Examples 1 to 4 and Comparative Examples 1 to 5 were cut into a width of 25 mm, and then double-sided tape was attached to a glass slide and rolled twice with a 2 kg roller. Under a temperature condition of 60°C, the coating was peeled off from the membrane at a speed of 300 mm / min at a distance of 90 mm from the membrane, and the average value of the 90° peel strength was measured. The measurement results are shown in Table 1 below.

[0159] [Table 1]

[0160] 90° peel strength (gf / 25mm) Example 1 45 Example 2 60 Example 3 35 Example 4 135 Comparative Example 1 - Comparative Example 2 10 Comparative Example 3 150 Comparative Example 4 25 Comparative Example 5 145

[0161] Experimental Example 2-High Temperature Safety Evaluation of Lithium Secondary Batteries

[0162] Each of the lithium secondary batteries manufactured in Examples 1 to 4 and Comparative Examples 1 to 5 was subjected to a hot box test. Figures 1 to 9 Specifically, the hot box test was performed as follows: the temperature was increased from 25°C at a rate of 10°C / min, and the temperature was maintained at 100°C, 120°C, 140°C, 150°C, 160°C, 170°C and 180°C for 30 minutes each, and then the temperature was increased to 200°C at a rate of 2°C / min.

[0163] Figures 1 to 4 is a graph showing the voltage-temperature changes over time of the lithium secondary batteries manufactured in Examples 1 to 4, Figures 5 to 9 is a graph showing the voltage-temperature changes over time of the lithium secondary batteries manufactured in Comparative Examples 1 to 5.

[0164] Furthermore, the ignition temperatures of the lithium secondary batteries of Examples 1 to 4 and Comparative Examples 1 to 5 in the hot box test are shown in Table 2 below.

[0165] [Table 2]

[0166] Fire start temperature (℃) Example 1 No fire Example 2 No fire Example 3 No fire Example 4 No fire Comparative Example 1 170 Comparative Example 2 173 Comparative Example 3 No fire Comparative Example 4 174 Comparative Example 5 No fire

[0167] like Figures 1 to 9 As shown in Table 2, it can be determined that in Examples 1 to 4, the 90° peel strength between the separator and the coating satisfies 30 gf / 25 mm to 140 gf / 25 mm, and even at high temperatures, due to the strong adhesion between the separator and the coating, the separator will not thermally shrink, so that the battery will not catch fire, and the battery has excellent high temperature safety.

[0168] On the other hand, it can be determined that, in the case of Comparative Example 1 in which no coating is formed on the separator, and Comparative Examples 2 and 4 in which the 90° peel strength between the separator and the coating is less than 30 gf / 25 mm, the separator thermally shrinks at high temperatures, the positive and negative electrodes short-circuit, and the battery catches fire at temperatures above 170°C.

[0169] Experimental Example 3-Evaluation of Cell Resistance of Lithium Secondary Batteries

[0170] The cell resistance value was measured for each of the lithium secondary batteries manufactured in Examples 1 to 4 and Comparative Examples 1 to 5, and the results are shown in Table 3 below.

[0171] Specifically, the lithium secondary battery was charged to 50% SOC at 0.1C constant current at 25°C and then discharged for 10 seconds at 1.5C constant current. The resistance value at 0.1 seconds and the resistance value between 0.1 seconds and 10 seconds were calculated from the voltage drop value generated at this time.

[0172] [Table 3]

[0173]

[0174] As shown in Table 3, it can be confirmed that for Examples 1 to 4 in which the 90° peel strength between the diaphragm and the coating satisfies 30 gf / 25 mm to 140 gf / 25 mm, the cell resistance value increases compared to Comparative Example 1 in which no coating is formed on the diaphragm, but the difference is not significant.

[0175] On the other hand, it can be determined that for Comparative Examples 3 and 5 in which the 90° peel strength between the separator and the coating is greater than 140 gf / 25 mm, the lithium ion conductivity at the interface between the separator and the coating is lower than that of Examples 1 to 4, and therefore the cell resistance is high.

Claims

1. An electrode assembly, comprising: positive electrode; negative electrode; a separator disposed between the positive electrode and the negative electrode; as well as a coating layer formed on one surface of the separator and comprising polymer particles or ceramic particles having a zeta potential of 25 mV or more, The 90° peel strength between the diaphragm and the coating is 30 gf / 25 mm to 140 gf / 25 mm.

2. The electrode assembly according to claim 1, wherein: The coating is in direct contact with the positive electrode.

3. The electrode assembly according to claim 1, wherein: The ratio D1 / D2 of the thickness of the coating layer (D1) to the thickness of the separator (D2) is 0.1 to 4.

4. The electrode assembly according to claim 1, wherein: The coating layer has a thickness (D1) of 30 μm or less.

5. The electrode assembly according to claim 1, wherein: The separator has a thickness (D2) of 5 μm to 20 μm.

6. The electrode assembly according to claim 1, wherein: The polymer particles include at least one selected from the group consisting of polyethylene oxide (PEO), polyphenylene sulfide (PPS), polyalkyl (meth)acrylate, polystyrene, polyvinyl chloride, polycarbonate, polysulfone, polyethersulfone, polyetherimide, polyphenylsulfone, polyamideimide, polyimide, polybenzimidazole, polyetherketone, polyphthalamide, polybutylene terephthalate and polyethylene terephthalate.

7. The electrode assembly according to claim 1, wherein: The ceramic particles include at least one selected from the group consisting of boehmite (γ-AlO(OH)), Al2O3, TiO2, Fe2O3, SiO2, ZrO2, Co3O4, SnO2, NiO, ZnO, V2O5, MnO, LAGP (lithium aluminum germanium phosphate) based compounds, LLZO (lithium lanthanum zirconium oxide) based compounds, LATP (lithium aluminum titanium phosphate) based compounds, LLZTO (lithium lanthanum zirconium tantalum oxide) based compounds, LLTO (lithium lanthanum titanium oxide) based compounds, LSTP (lithium silicon titanium phosphate) based compounds, LGPO (lithium germanium phosphate) based compounds and lithium oxide (e.g., Li2O).

8. The electrode assembly according to claim 1, wherein: The polymer particles or the ceramic particles have an average particle size (D 50 ).

9. The electrode assembly according to claim 1, wherein: The coating layer includes a polymer binder and the polymer particles or the ceramic particles dispersed on the polymer binder.

10. The electrode assembly according to claim 9, wherein: The coating layer includes the polymer binder and the polymer particles in a weight ratio of 1:9 to 5:5, or the coating layer includes the polymer binder and the ceramic particles in a weight ratio of 1:9 to 5:

5.

11. A lithium secondary battery, comprising: The electrode assembly according to any one of claims 1 to 10; as well as A flame retardant electrolyte comprises a flame retardant solvent having a flash point of 100° C. or above or having no flash point and a lithium salt.

12. The lithium secondary battery according to claim 11, wherein: The flame retardant solvent includes at least one organic solvent having a functional group selected from the group consisting of a sulfone functional group, a fluorine-containing functional group, a phosphorus-containing functional group, and a nitrile functional group.

13. The lithium secondary battery according to claim 11, wherein: The flame retardant solvent includes at least one organic solvent selected from the group consisting of a sulfone-based compound, a nitrile-based compound, a phosphoric acid-based compound, and a fluorine-substituted carbonate-based compound.

Citation Information

Patent Citations

  • Artificial intelligence robotics instrument playing technology and music education system using the same

    KR1020220113106A

  • Unmanned automatic fried cooking booth

    KR1020230117680A